Investigação da dopagem anódica de filmes de Al203 com zinco pelo processo de oxidação eletrolítica a plasma (PEO) - Martins, Gabriel Moraes Reche (Universidade Federal de São Carlos, 2023)
With the growing demand for a healthier life, there is a great interest in materials that can eliminate pathogenic microorganisms. A great number of inorganic bactericidal materials are found as metallic nanoparticles and nanoparticles of metallic oxides such as silver, gold, copper, titanium oxide, and zinc oxide. Thus, this work was intended to explore the incorporation of zinc oxide through the process of plasma electrolytic oxidation in a commercial aluminum alloy. Zinc oxide can be inserted in the matrix or on the surface of various materials in several ways, depending on the application. In special to the treatment of metallic surfaces, an approach that has been explored is the method of anodization of metals in the plasma electrolytic oxidation (PEO) regime. It was used as a substrate, a commercial aluminum alloy. The electrolytic solutions used were: I – Oxalic acid and NH4OH; II – Dihydrate acetate zinc, EDTA salt disodium 2H2O, and NH4OH; III – Citric acid; IV – Citric acid and Dihydrate acetate zinc. The working temperature was set at 20 °C, and the current density used in the process was 10 mA cm-2. The anodization was realized through a galvanostatic process in an anodization reactor with a glass recipient for the thermostatic bath and socket for two platinum counter electrodes with constant agitation by a magnetic agitator. To verify the morphological and compositional properties of formed oxides, it was used image and analysis techniques. The electronic micrographs and compositional analysis data by EDS were obtained using scanning electron microscopy. The results demonstrated for electrolyte I, the anodization curves associated with the appearance of the PEO process, was possible to realize the PEO process in the aluminum alloy used as substrate. For electrolyte II, the anodization curves associated with the appearance of the PEO process show an unstable system for the electrolyte; that is, it’s not possible the reproduction of the observed phenomenon. Furthermore, it’s observed by the anodization curves that it wasn’t possible to obtain the PEO process for the base electrolyte. For electrolytes III and IV, observing the anodization curves with the process observation and frontal micrographs, it’s possible to affirm that there was, in a reproducible and stable way, the PEO process and formation of a porous oxide film in the surface of the substrate. However, it was not possible to perceive, in the analyzed points, the incorporation or doping of the Zinc element by electrolyte IV.
Investigation of anodic doping of Al203 films with zinc by plasma electrolytic oxidation (PEO) process
Keywords: Plasma Electrolytic Oxidation (PEO); Alumínio; Óxido de Zinco; Dopagem Anódica; CIENCIAS EXATAS E DA TERRA::QUIMICA